MEMBACA ULANG METODOLOGI TAFSIR IBNU KATSIR DALAM MENAFSIRKAN AL-QUR’AN - Sunaryanto (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
Ibn Kathir's interpretation is a product of interpretation produced in pre-contemporary times. However, this interpretation seems to be the book of Tafsir A-Qur'an which is mostly used as a reference in the interpretation of the Al-Qur'an. The purpose of writing this paper is to review Ibn Kathir's methodology of interpretation in Ibn Kathir's Tafsir. The method of writing this paper is to use library research (library research). The conclusion of this paper is that Ibn Kathir's Tafsir in his tafsir methodology uses the bi al-ma'tsur / bi ar-riwayah tafsir approach and also the tahlili (analytical) approach. Ibn Kathir is very dominant in using narrations / hadiths.